The cardinal of the Kremlin - Clancy, Tom, 1947-2013. (New York : Berkley Books, 1989)
Jack Ryan, CIA analyst, must rescue Colonel Filitov, America's highest agent in the Kremlin, from the KGB as the race to build the first Star Wars missile defense system continues.
Keywords: Ryan, Jack, -- Sr. (Fictitious character) -- Fiction; Intelligence service -- United States -- Fiction